Resin particle, toner, toner storage unit, image forming apparatus, and image forming method
Resin particles with a core-shell structure and high biomass/recycled content address the challenge of low-temperature fixability and heat-resistant storage stability, enhancing toner performance and environmental friendliness.
Patent Information
- Application Number
- JP2024105208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-20
AI Technical Summary
Conventional toners face challenges in achieving both low-temperature fixability and heat-resistant storage stability while reducing environmental impact, particularly when using biomass-derived resins.
The development of resin particles with a core-shell structure, comprising a core resin made of crystalline resin and a shell resin, where the total mass proportion of biomass-derived and recycled PET/PBT-derived resins is 30% or more, incorporating C2-C4 straight chain aliphatic alcohol and C10-C12 linear aliphatic acids to enhance low-temperature fixing properties and heat-resistant storage stability.
The resin particles achieve excellent low-temperature fixability and heat-resistant storage stability while minimizing environmental burden, utilizing a high proportion of biomass and recycled materials.
Smart Images

Figure 2025010039000004 
Figure 2025010039000005 
Figure 2025010039000001
Abstract
Description
[Technical field]
[0001] The present invention relates to resin particles, a toner, a toner storage unit, an image forming apparatus, and an image forming method. [Background technology]
[0002] In recent years, there has been a demand for toners that have a lower environmental impact. To meet this demand, for example, the reduction of power consumption by improving the low-temperature fixing ability of the toner itself, the reduction of energy used in the toner manufacturing process, and the use of plant (biomass)-derived resins as binder resins are being considered.
[0003] In recent years, the need for resource conservation, energy conservation, and recycling of resources has become important as the use of energy expands with the increase in population and resources become depleted. Local governments have begun to recycle PET (polyethylene terephthalate) bottles and PBT (polybutylene terephthalate) bottles, and they are beginning to be used as raw materials for various types of clothing and containers, and there is a high demand for the development of new applications that allow the reuse of recycled PET, etc. From this perspective, toner binder resins are manufactured as recovered polyethylene terephthalate raw materials, and toners containing this (recycled toners) are known.
[0004] Nowadays, there is a strong demand for toners that are more environmentally friendly and have improved functionality, including the use of plant-derived resins. However, when low-temperature fixability is required, heat-resistant storage stability tends to deteriorate.
[0005] Patent Document 1 discloses a toner containing a large amount of crystalline resin containing biomass, and Patent Document 2 discloses a resin containing a biological resin that is acidified by combining an amorphous polyester resin derived from a biological source with an acid derived from a biological source. Patent Document 3 discloses a toner in which the shape of the domain of the crystalline resin containing biomass in the toner is specified. Summary of the Invention [Problem to be solved by the invention]
[0006] The above-mentioned conventional toners are not satisfactory in terms of reducing the burden on the environment as mentioned above, and in terms of toner qualities such as low-temperature fixability and heat-resistant storage stability. An object of the present invention is to provide resin particles which have a low environmental impact and excellent low-temperature fixability and heat-resistant storage stability. [Means for solving the problem]
[0007] The present invention relates to resin particles as described below. At least C2-C4 linear aliphatic alcohol / C 10 -C 12 Resin particles containing a resin C derived from biomass consisting of a linear aliphatic acid and a resin B containing a component derived from polyethylene terephthalate (PET) and / or polybutylene terephthalate (PBT), The resin particles have a core-shell structure consisting of a core resin and a shell resin, The core resin comprises a crystalline resin, The resin particles are characterized in that the total ratio of the resin C and the resin B in 100% by mass of the resin particles is 30% by mass or more. Effect of the Invention
[0008] According to the present invention, it is possible to provide resin particles which have a low environmental impact and excellent low-temperature fixability and heat-resistant storage stability. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The resin particles of the present invention have a core-shell structure consisting of a core resin and a shell resin. In order to make resin particles environmentally friendly, it is necessary to introduce more biomass resin or recycled resin into the resin particles, and it is required to use biomass resin or recycled resin not only for the core amorphous resin but also for the shell and other materials.
[0011] The core resin is a C2-C4 linear aliphatic alcohol and C 10 -C 12 It is preferable that the polyester contains a polyester made of a linear aliphatic acid of the formula C2-C4. The linear aliphatic alcohol of C2-C4 has the same carbon number as ethylene glycol and butanediol derived from PET and PBT, which are common recycled resins, and has high affinity, so it has the effect of easily achieving low-temperature fixability. 10 -C 12 The straight chain aliphatic acid is preferred from the standpoint of thermal properties, handling properties and cost required for a resin toner.
[0012] When terephthalic acid or isophthalic acid derived from recycled polyethylene terephthalate (hereinafter referred to as "PET") or polybutylene terephthalate (hereinafter referred to as "PBT") is used, the aromatic ring structure of terephthalic acid or isophthalic acid makes it possible to compensate for the strength of the toner and achieve heat resistance and storage stability, even though the issue of heat resistance and storage stability is disadvantageous due to low-temperature fixing. If the ratio of biomass-derived resin and resin containing terephthalic acid and isophthalic acid in the resin particles is 30% by mass or more, it is likely to be recognized as having a high environmental effect. Furthermore, by increasing the resin ratio to 50% or more by mass, the environmental effects can be significantly improved, and the impact on society will be greater.
[0013] The resin particles and toner according to the present invention will be described below. Note that the present invention is not limited to the following embodiments, and may be modified, added, modified, deleted, or otherwise altered within the scope of what a person skilled in the art can conceive, and any embodiment is within the scope of the present invention as long as it exhibits the functions and effects of the present invention.
[0014] The resin particles of the present invention can be produced as follows. (Oil phase preparation process) In the method for producing resin particles of the present invention, an oil phase is first prepared by dissolving or dispersing a resin, a colorant, a crosslinking component, a wax, etc. in an organic solvent. The oil phase can be prepared by gradually adding the resin, the colorant, etc. to an organic solvent while stirring, and dissolving or dispersing them. A known dispersion means can be used, for example, a dispersing machine such as a bead mill or a disk mill. The materials used in the oil phase preparation step will be described.
[0015] <Biomass-derived resin> Biomass-derived resin is a resin containing a plant-derived compound as a raw material, and corresponds to biomass-derived resin C of the present invention. By adjusting the ratio of petroleum-derived and plant-derived alcohol and acid components, it is possible to adjust the environmental compatibility ratio and toner quality. The amount of biomass resin in the present invention is calculated from the amount of monomer charged during production. If the resin monomer composition is unknown, radiocarbon isotope analysis can be performed using the following methods. 14 This is possible by specifying the C concentration and monomer.
[0016] (Radioactive carbon isotopes 14 C concentration) Radioactive carbon isotopes of resin particles according to an embodiment 14 C concentration (hereinafter referred to as “ 14 The carbon concentration of the resin particles is preferably 10.8 pMC or more, more preferably 11 pMC or more, more preferably 20 pMC or more, and even more preferably 30 pMC or more. 14 If the C concentration is less than 10.8 pMC, it is generally likely to be recognized as having a low biomass degree (described later), and a reduction in the burden on the environment cannot be achieved.
[0017] 14 C concentration exists in nature (in the atmosphere) and is taken up by plants through photosynthesis while they are active and exists in the atmosphere.14 However, once the organism ceases to function, photosynthesis ceases and the carbon dioxide in the atmosphere is no longer absorbed. 14 According to the half-life of C, 5,730 years, 14 The C concentration decreases. Fossil resources derived from living organisms are from tens of thousands to hundreds of millions of years old, so 14 C concentration is barely detectable.
[0018] Here, "pMC" is an abbreviation for percent modern carbon, which is the percentage of biomass in 1950. 14 C and 12 Ratio to C ( 14 C / 12 C) is defined as 100 pMC. 14 Since the C concentration is increasing year by year, it is stipulated that this value must be multiplied by a coefficient for correction purposes. The correction coefficient to be used is the coefficient appropriate for that year.
[0019] 14 The C concentration can also be expressed as the biomass degree calculated by the following formula (1). Biomass ratio (%) = 14 C concentration (pMC) / 107.5×100...Equation (1) 14 A C concentration of 10.8 pMC or more means that the biomass ratio is 10% or more. The biomass ratio of 10% or more is a concentration desired from the standpoint of carbon neutrality.
[0020] 14 The method for measuring the C concentration is not particularly limited and can be appropriately selected depending on the purpose, but radiocarbon dating is particularly preferred. The procedure for radiocarbon dating involves burning resin particles, reducing the carbon dioxide (CO2) and obtaining graphite (C). 14The C concentration is measured using an accelerator mass spectrometry (AMS, manufactured by Beta Analytic Corp.) Measurement using this AMS is disclosed in, for example, Japanese Patent No. 4050051.
[0021] <Recycled resin> The components derived from recycled resin used in the present invention are processed from recycled PET and PBT, which are one of the raw materials. For example, recycled PET and PBT products processed into flakes, and terephthalic acid, isophthalic acid, and ethylene glycol obtained by chemical recycling are included. There are no limitations on the molecular weight distribution, composition, manufacturing method, and form when used of PET and PBT. In addition, the recycled resin in the present invention includes not only recycled resin products, but also those that have not been commercialized, such as off-spec fiber waste and pellets. The environmental response ratio and toner quality can be adjusted by adjusting the introduction ratio of terephthalic acid, isophthalic acid, and ethylene glycol during polyester resin synthesis.
[0022] (amorphous resin) The amorphous resin is preferably an amorphous polyester resin, more preferably a linear polyester resin, more preferably an unmodified polyester resin, and even more preferably an environmentally friendly resin. The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, and is not modified with an isocyanate compound or the like. The amorphous polyester resin preferably does not contain a urethane bond or a urea bond.
[0023] <Amorphous polyester resin> The amorphous polyester resin preferably contains a dicarboxylic acid component as a constituent, and the dicarboxylic acid component preferably contains 50 mol % or more of terephthalic acid, which is advantageous in terms of heat-resistant storage stability.
[0024] Examples of the polyhydric alcohol include diols. Examples of the diol include alkylene (carbon number: 2 to 3) oxide (average number of moles added: 1 to 10) adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane and polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, propylene glycol; hydrogenated bisphenol A, and alkylene (carbon number: 2 to 3) oxide (average number of moles added: 1 to 10) adducts of hydrogenated bisphenol A. These may be used alone or in combination of two or more.
[0025] Examples of the polycarboxylic acid include dicarboxylic acids. Examples of the dicarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, and succinic acids substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, such as dodecenylsuccinic acid and octylsuccinic acid.
[0026] Among these, succinic acid, which is a saturated aliphatic acid derived from plants, is preferred. Being derived from plants can enhance carbon neutrality. Saturated aliphatic groups have the effect of enhancing the recrystallization properties of crystalline polyester resins, thereby increasing the aspect ratio of the crystalline polyester resins and improving low-temperature fixability. These may be used alone or in combination of two or more.
[0027] In order to adjust the acid value and hydroxyl value, the amorphous polyester resin B may contain at least one of a trivalent or higher carboxylic acid and a trivalent or higher alcohol at the end of the resin chain. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and anhydrides thereof, etc. Examples of the trivalent or higher alcohol include glycerin, pentaerythritol, trimethylolpropane, etc.
[0028] <Amorphous polyester resin B> In order to adjust the environmentally friendly ratio, it is preferable to use plant-derived alcohol and acid components as the amorphous polyester resin B used in the present invention. At the same time, it is preferable to use a polyester resin synthesized from terephthalic acid, isophthalic acid, and ethylene glycol derived from PET and / or PBT. It is also preferred that Resin B contains structural units derived from terephthalic acid and structural units derived from isophthalic acid, with the ratio of the structural units derived from isophthalic acid to the structural units derived from terephthalic acid being 1 percent or more.
[0029] It is preferable to use ethylene glycol or propylene glycol as the plant-derived alcohol component, and terephthalic acid or succinic acid as the acid component, but there is no particular limitation to these, and there is no limitation as long as the component is plant-derived.
[0030] The molecular weight of the amorphous polyester resin B is not particularly limited and can be appropriately selected depending on the purpose. In the measurement by GPC (gel permeation chromatography), the weight average molecular weight (Mw) is preferably 3,000 to 10,000. The number average molecular weight (Mn) is preferably 1,000 to 4,000. The Mw / Mn is preferably 1.0 to 4.0.
[0031] When the molecular weight is equal to or more than the lower limit, it is possible to suppress a decrease in the heat-resistant storage stability of the toner and in the durability against stress such as stirring in a developing machine, etc. When the molecular weight is equal to or less than the upper limit, it is possible to suppress an increase in the viscoelasticity of the toner when melted, and to suppress a decrease in the low-temperature fixability.
[0032] The weight average molecular weight (Mw) is more preferably from 4000 to 7000. The number average molecular weight (Mn) is more preferably from 1500 to 3000. The Mw / Mn is more preferably from 1.0 to 3.5.
[0033] The acid value of the amorphous polyester resin B is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 mgKOH / g or more and 50 mgKOH / g or less, and more preferably 5 mgKOH / g or more and 30 mgKOH / g or less. When the acid value is 1 mgKOH / g or more, the toner is easily negatively charged, and further, when fixed to paper, the affinity between the paper and the toner is improved, and low-temperature fixability can be improved. When the acid value is 50 mgKOH / g or less, the charge stability, particularly the charge stability against environmental changes, can be suppressed from decreasing. The hydroxyl value of the amorphous polyester resin B is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.
[0034] The glass transition temperature (Tg) of the amorphous polyester resin B is preferably 40° C. to 80° C., more preferably 50° C. to 70° C. When the glass transition temperature is 40° C. or higher, the toner has sufficient heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has good filming resistance. When the glass transition temperature is 80° C. or lower, the toner is sufficiently deformed by heating and pressure during fixing, and has good low-temperature fixing properties.
[0035] The molecular structure of the amorphous polyester resin B can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 and 990±10cm -1 One method is to detect amorphous polyester resins that do not have absorption due to olefin δCH (out-of-plane bending vibration).
[0036] The content of the amorphous polyester resin B is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50 parts by mass or more and 90 parts by mass or less, and more preferably 60 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the toner. When the content is 50 parts by mass or more, the dispersibility of the pigment and the release agent in the toner can be suppressed from deteriorating, and the occurrence of fogging and disturbance of the image can be suppressed. When the content is 90 parts by mass or less, the content of the polyester resin C and other polyester resins (hereinafter referred to as "amorphous polyester resin A") can be prevented from decreasing, and the low-temperature fixability can be suppressed from decreasing. When the content is in the above-mentioned more preferred range, it is advantageous in that both high image quality and low-temperature fixability are excellent.
[0037] (Polyester resin C) The polyester resin C used in the present invention will be described below. The polyester resin C has high crystallinity and therefore exhibits thermal melting characteristics that cause a sudden change in viscosity near the fixing start temperature.
[0038] By using the polyester resin C having such properties together with the amorphous polyester resin B, a toner having both good heat-resistant storage stability and low-temperature fixability can be obtained. For example, when used together, the heat resistance storage property is good due to the crystallinity up to just before the melting start temperature, and at the melting start temperature, a sudden viscosity drop (sharp melt property) occurs due to the melting of polyester resin C, which in turn becomes compatible with the aforementioned amorphous polyester resin B, and both of them undergo a sudden viscosity drop, allowing for good fixation.
[0039] Crystalline polyester resins are obtained from polyhydric alcohols and polycarboxylic acids such as polycarboxylic acids, polycarboxylic anhydrides, and polycarboxylic esters, or derivatives thereof. Note that, in the present invention, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid such as polycarboxylic acids, polycarboxylic anhydrides, and polycarboxylic esters, or derivatives thereof, as described above, and modified polyester resins, such as prepolymers and resins obtained by subjecting the prepolymers to crosslinking and / or elongation reactions, do not belong to the crystalline polyester resins.
[0040] <<Polyhydric alcohol>> The polyhydric alcohol is preferably a linear saturated aliphatic diol having a carbon number of 2 to 4. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in the melting point.
[0041] Examples of the linear saturated aliphatic diol include ethylene glycol, 1,3-propanediol, and 1,4-butanediol. Among these, ethylene glycol and 1,4-butanediol are preferred because the crystalline polyester resin has high crystallinity and excellent sharp melting properties. These may be used alone or in combination of two or more.
[0042] <<Polycarboxylic acids>> The polycarboxylic acid is preferably a linear saturated fatty acid having a carbon number of 10 to 12. Examples of the polycarboxylic acid include saturated aliphatic dicarboxylic acids such as 1,10-decanedicarboxylic acid and 1,12-dodecanedicarboxylic acid. From the viewpoint of carbon neutrality, plant-derived saturated aliphatic fatty acids having a carbon number of 12 or less are preferred. These may be used alone or in combination of two or more.
[0043] The polyester resin C is preferably composed of a linear saturated aliphatic diol having 2 to 4 carbon atoms and a linear saturated aliphatic dicarboxylic acid having 10 to 12 carbon atoms, which provides high crystallinity and excellent sharp melting properties, thereby enabling the resin to exhibit excellent low-temperature fixing properties. In addition, as a method for controlling the crystallinity and softening point of a crystalline polyester resin, there can be mentioned a method for designing and using a non-linear polyester obtained by adding a trivalent or higher polyhydric alcohol such as glycerin to the alcohol component during polyester synthesis, or a trivalent or higher polycarboxylic acid such as trimellitic anhydride to the acid component, and carrying out condensation polymerization.
[0044] The molecular structure of the polyester resin C of the present invention can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc., but it can be conveniently confirmed by infrared absorption spectrum at 965±10 cm -1 Or 990±10cm -1 Examples include those that have absorption due to the δCH (out-of-plane bending vibration) of olefins.
[0045] Regarding the molecular weight, from the viewpoint that a low molecular weight with a sharp molecular weight distribution has excellent low-temperature fixability, and that a large amount of low molecular weight components deteriorates heat-resistant storage stability, it has been found through extensive investigation that, in the molecular weight distribution by GPC of the o-dichlorobenzene soluble portion, the molecular weight distribution chart with the horizontal axis being log(M) and the vertical axis being weight % has a peak position in the range of 3.5 to 4.0, the half-width of the peak is 1.5 or less, the weight average molecular weight (Mw) is 3,000 to 30,000, the number average molecular weight (Mn) is 1,000 to 10,000, and Mw / Mn is 1 to 10. More preferably, the weight average molecular weight (Mw) is 5,000 to 15,000, the number average molecular weight (Mn) is 2,000 to 10,000, and Mw / Mn is 1-5.
[0046] From the viewpoint of affinity between paper and resin, the acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more to achieve the desired low-temperature fixability, more preferably 7 mgKOH / g or more to prepare fine particles by phase inversion emulsification, while it is preferably 45 mgKOH / g or less to improve hot offset properties. The hydroxyl value of the crystalline polymer is preferably 0 mgKOH / g or more and 50 mgKOH / g or less to achieve a predetermined low-temperature fixability and good charging properties, and more preferably 5 mgKOH / g or more and 50 mgKOH / g or less.
[0047] (Coloring agent) As the colorant in the present invention, known dyes and pigments can be used, for example, carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoi Andrinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Kanmin BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Tocarmine 6B, Pogment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, lithopone and mixtures thereof can be used.
[0048] (Organic solvent) The organic solvent is preferably volatile and has a boiling point of less than 100° C., since this makes it easier to remove the organic solvent later. Examples of such organic solvents include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, and isopropyl alcohol, which can be used alone or in combination. When the resin to be dissolved or dispersed in the organic solvent is a resin having a polyester skeleton, it is preferable to use an ester-based solvent such as methyl acetate, ethyl acetate, or butyl acetate, or a ketone-based solvent such as methyl ethyl ketone or methyl isobutyl ketone, because of their high solubility, and among these, methyl acetate, ethyl acetate, and methyl ethyl ketone, which have high solvent removability, are particularly preferable.
[0049] (Prepolymer) The present invention may contain a prepolymer. The reactive precursor may be a polyester having a group capable of reacting with an active hydrogen group. Examples of the group capable of reacting with an active hydrogen group include an isocyanate group, an epoxy group, a carboxylic acid, and an acid chloride group. Among these, an isocyanate group is preferred because it can introduce a urethane bond or a urea bond into the amorphous polyester resin. The reactive precursor may have a branched structure imparted by at least one of a trivalent or higher alcohol and a trivalent or higher carboxylic acid.
[0050] The polyester resin containing an isocyanate group may be, for example, a reaction product of a polyester resin having an active hydrogen group and a polyisocyanate. The polyester resin having an active hydrogen group may be obtained by polycondensation of a diol, a dicarboxylic acid, and at least one of a trivalent or higher alcohol and a trivalent or higher carboxylic acid. The trivalent or higher alcohol and the trivalent or higher carboxylic acid impart a branched structure to the polyester resin containing an isocyanate group.
[0051] Examples of the diol include aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylol. Examples of the diol include diols having an oxyalkylene group such as ethylene glycol; alicyclic diols such as 1,4-cyclohexanedimethanol and hydrogenated bisphenol A; alicyclic diols to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added; bisphenols such as bisphenol A, bisphenol F, and bisphenol S; and alkylene oxide adducts of bisphenols such as those to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added. Among these, from the viewpoint of controlling the glass transition point of the polyester resin (A) to 20° C. or less, it is preferable to use aliphatic diols having a carbon number of 3 to 10 such as 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, and 3-methyl-1,5-pentanediol, and it is more preferable to use 50 mol% or more of the alcohol component in the resin. These diols may be used alone or in combination of two or more.
[0052] The polyester resin A is preferably an amorphous resin, and the melt viscosity during fixing is reduced by providing steric hindrance to the resin chain, which makes it easier to achieve low-temperature fixing properties. For this reason, the main chain of the aliphatic diol preferably has a structure represented by the following general formula (1). [ka] [In the formula, R1 and R2 each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an odd number from 3 to 9. However, in the n repeating units, R1 and R2 may be the same or different.]
[0053] Here, the main chain of the aliphatic diol in the present invention refers to a carbon chain that connects two hydroxyl groups of the aliphatic diol with the shortest number of carbon atoms. When the carbon number of the main chain is odd, the crystallinity decreases due to the odd-even nature, which is preferable. In addition, when the main chain has at least one alkyl group having 1 to 3 carbon atoms in the side chain, the interaction energy between the main chain molecules decreases due to the steric nature, which is more preferable.
[0054] Examples of the dicarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, dodecanedioic acid, maleic acid, and fumaric acid; and aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. In addition, anhydrides, lower (1 to 3 carbon atoms) alkyl esters, and halides of these may be used. Among these, from the viewpoint of controlling the Tg of the polyester resin A to 20° C. or less, aliphatic dicarboxylic acids having 4 to 12 carbon atoms are preferred, and it is more preferred to use them in an amount of 50% by mass or more of the carboxylic acid component in the resin. These dicarboxylic acids may be used alone or in combination of two or more.
[0055] Examples of the trihydric or higher alcohol include trihydric or higher aliphatic alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and sorbitol; trihydric or higher polyphenols such as trisphenol PA, phenol novolac, and cresol novolac; and alkylene oxide adducts of trihydric or higher polyphenols, such as those obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to trihydric or higher polyphenols.
[0056] Examples of the trivalent or higher carboxylic acid include trivalent or higher aromatic carboxylic acids, and particularly preferred are trivalent or higher aromatic carboxylic acids having 9 to 20 carbon atoms, such as trimellitic acid and pyromellitic acid. In addition, anhydrides, lower (carbon number 1 to 3) alkyl esters, and halides of these may also be used.
[0057] Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates. The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. For example, 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-tolylene diisocyanate (TDI), crude TDI, 2,4'- and / or 4,4'-diphenylmethane diisocyanate (MDI), crude MDI [crude diaminophenylmethane [condensation product of formaldehyde and aromatic amine (aniline) or a mixture thereof; diaminodiphenylmethane and a small amount (for example, 5 to 20% by mass) of a trifunctional or more functional compound, Phosgenates of the above polyamines and mixtures thereof: polyallyl polyisocyanate (PAPI), aromatic diisocyanates such as 1,5-naphthylene diisocyanate, 4,4',4"-triphenylmethane triisocyanate, m- and p-isocyanatophenylsulfonyl isocyanate; ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), dodecamethylene diisocyanate, 1,6,11-undecane triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, etc. Aliphatic diisocyanates such as isocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate; isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), bis(2-isocyanato alicyclic diisocyanates such as 2,5- and 2,6-norbornane diisocyanate, m- and p-xylylene diisocyanate (XDI), α,α,α',α'-tetramethylxylylene diisocyanate (TMXDI), and other aromatic aliphatic diisocyanates; trivalent or higher polyisocyanates such as lysine triisocyanate and diisocyanate modified products of trivalent or higher alcohols; and modified products of these isocyanates, and mixtures of two or more of these may also be used.Examples of the modified isocyanate include modified products containing a urethane group, a carbodiimide group, an allophanate group, a urea group, a biuret group, a uretdione group, a uretoimine group, an isocyanurate group, and an oxazolidone group.
[0058] A charge control agent and the like may be added to the oil phase.
[0059] (Charge control agent) Any of the known charge control agents can be used, such as nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives. Specifically, these include the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (all manufactured by Hodogaya Chemical Co., Ltd.), the quaternary ammonium salt Copy Charge PSY VP2038, the triphenylmethane derivative Copy Blue PR, the quaternary ammonium salt Copy Charge NEG VP2036, and Copy Charge NX. Examples of the charge control agent include VP434 (all manufactured by Hoechst), LRA-901, boron complex LR-147 (manufactured by Nippon Carlit), copper phthalocyanine, perylene, quinacridone, azo pigments, and polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts. The charge control agent may be used in an amount that allows the agent to exhibit its performance without interfering with fixability, etc., and is contained in the toner in an amount of 0.5% by mass to 5% by mass, and preferably 0.8% by mass to 3% by mass.
[0060] (wax) The wax is not particularly limited and can be appropriately selected depending on the purpose, but a release agent having a low melting point of 50° C. to 120° C. is preferable. The release agent having a low melting point effectively acts as a release agent between the fixing roller and the toner interface by being dispersed in the resin, and as a result, the hot offset property is good even in an oil-less case (a release agent such as oil is not applied to the fixing roller).
[0061] Suitable examples of the release agent include waxes. Examples of the waxes include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, wood wax, and rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusine; and petroleum waxes such as paraffin, microcrystalline, and petrolatum. In addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax and polyethylene wax; synthetic waxes such as esters, ketones, and ethers; and the like. Furthermore, fatty acid amides such as 12-hydroxystearic acid amide, stearic acid amide, phthalic anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups on the side chains may be used. These may be used alone or in combination of two or more. From the viewpoint of reducing the environmental load, vegetable waxes are preferred.
[0062] The melting point of the wax is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50°C to 120°C, more preferably 60°C to 90°C. If the melting point is 50°C or higher, the wax can be prevented from adversely affecting the heat-resistant storage stability, and if the melting point is 120°C or lower, the problem of cold offset occurring during fixing at low temperatures can be effectively prevented. The melt viscosity of the wax is preferably 5 cps to 1,000 cps, more preferably 10 cps to 100 cps, as measured at a temperature 20°C higher than the melting point of the wax. If the melt viscosity is 5 cps or higher, the release property can be prevented from decreasing, and if it is 1,000 cps or lower, the effects of hot offset resistance and low-temperature fixability can be fully exhibited. The content of the wax in the toner is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0% by mass to 40% by mass, more preferably 3% by mass to 30% by mass.
[0063] <Method of manufacturing resin particles> The method for producing resin particles according to an embodiment will be described. The method for producing resin particles according to an embodiment includes an oil phase preparation step, an aqueous phase preparation step, a phase inversion emulsification step, a solvent removal step, an aggregation step, and a fusion step, and further includes other steps such as a shell formation step, a washing step, a drying step, an annealing step, and an external addition step, as necessary.
[0064] (Oil phase preparation process) In the oil phase preparation step, first, the resin (amorphous resin, amorphous resin and crystalline resin, etc.) which is the raw material of the resin particles, and further materials such as colorant, prepolymer (precursor of amorphous polyester resin A), wax, etc., are dissolved or dispersed in an organic solvent to prepare an oil phase. Note that a part of the materials may be added in the aggregation step described later. The method for preparing the oil phase is not particularly limited and can be appropriately selected depending on the purpose. For example, a method in which raw materials such as a resin are gradually added to an organic solvent with stirring to dissolve or disperse the raw materials can be mentioned. For dispersion, known dispersing machines such as a bead mill and a disk mill can be used.
[0065] The raw materials used in the oil phase preparation step can be those described in the above section on <Resin Particles>. These may be used alone or in combination of two or more. At least one of the resins (amorphous resin, amorphous resin, and crystalline resin) is preferably a biomass-derived resin.
[0066] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but a volatile solvent having a boiling point of less than 100° C. is preferred because it makes it easier to remove the organic solvent later. Examples of such organic solvents include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, and isopropyl alcohol. These may be used alone or in combination of two or more.
[0067] When the resin to be dissolved or dispersed in the organic solvent is a resin having a polyester skeleton, the organic solvent is preferably an ester solvent such as methyl acetate, ethyl acetate, or butyl acetate, or a ketone solvent such as methyl ethyl ketone or methyl isobutyl ketone, because of its high solubility. Among these, the organic solvent is preferably methyl acetate, ethyl acetate, or methyl ethyl ketone, because of its high solvent removability. The amount of organic solvent used is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 40 parts by mass or more and 300 parts by mass or less, more preferably 60 parts by mass or more and 140 parts by mass or less, and even more preferably 80 parts by mass or more and 120 parts by mass or less, relative to 100 parts by mass of the raw material for the resin particles.
[0068] (Aqueous phase preparation process) In the aqueous phase preparation step, an aqueous phase (aqueous medium) is prepared. The aqueous medium is not particularly limited and can be appropriately selected from known ones, for example, water, a solvent miscible with water, or a mixture thereof. From the viewpoint of granulation, the organic solvent concentration is preferably equal to or less than the saturated concentration in ion-exchanged water.
[0069] The water-miscible solvent is not particularly limited and can be appropriately selected from known solvents, such as alcohol, dimethylformamide, tetrahydrofuran, cellosolves, lower ketones, and esters. Examples of the alcohol include methanol, isopropanol, and ethylene glycol. Examples of lower ketones include acetone and methyl ethyl ketone. An example of the esters is ethyl acetate. These may be used alone or in combination of two or more.
[0070] (Phase inversion emulsification process) In the phase inversion emulsification step, the oil phase obtained in the oil phase preparation step is atomized. After neutralizing the oil phase, ion-exchanged water is added to the neutralized oil phase, and a fine particle dispersion is obtained by phase inversion emulsification, in which the water-in-oil dispersion is inverted into an oil-in-water dispersion. The phase inversion emulsification is carried out by stirring. This is carried out by uniformly mixing and dispersing using a conventional stirrer or dispersing device.
[0071] The stirring blade is not particularly limited and can be appropriately selected according to the viscosity of the solution. Examples include low-viscosity stirring blades such as paddles and propellers, medium-viscosity stirring blades such as anchors and Maxblends, and high-viscosity stirring blades such as helical ribbons. The dispersion device is not particularly limited and can be an ultrasonic disperser, a bead mill, a ball mill, a roll mill, a homomixer, an ultramixer, a disperser mixer, a penetrating type high-pressure dispersion device, a collision type high-pressure dispersion device, a multi-hole type high-pressure dispersion device, an ultrahigh-pressure homogenizer, an ultrasonic homogenizer, etc. A normal stirrer and a dispersion device may be used in combination. Among these, paddle and anchor are preferred since they can control the volume average particle size of the dispersion (oil droplets) within the above-mentioned preferred range.
[0072] The base for neutralizing the oil phase may be either a basic inorganic compound or a basic organic compound. Examples of the basic inorganic compound include sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonia, sodium carbonate, sodium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, and ammonia. Examples of the basic organic compound include N,N-dimethylethanolamine, N,N-diethylethanolamine, triethanolamine, tripropanolamine, tributanolamine, triethylamine, n-propylamine, n-butylamine, isopropylamine, monomethanolamine, morpholine, methoxypropylamine, pyridine, vinylpyridine, and isophoronediamine.
[0073] When a stirring blade is used, the conditions such as the rotation speed, stirring time, and stirring temperature are not particularly limited and can be appropriately selected depending on the purpose. The rotation speed is not particularly limited, but is preferably 100 rpm to 1,000 rpm, and more preferably 200 rpm to 600 rpm. The stirring time and the stirring temperature are not particularly limited and may be appropriately selected depending on the purpose.
[0074] Also, a dispersant may be used if necessary. The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.
[0075] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. For example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used. The anionic surfactant is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include alkylbenzene sulfonate, α-olefin sulfonate, phosphate, etc. Among these, those having a fluoroalkyl group are preferred.
[0076] (Solvent removal) In order to remove the organic solvent from the obtained colored fine particle dispersion, a method can be adopted in which the temperature of the entire system is gradually raised while being stirred, and the organic solvent in the droplets is completely evaporated and removed. Alternatively, the obtained colored particle dispersion may be sprayed into a dry atmosphere while stirring to completely remove the organic solvent from the droplets. Alternatively, the colored particle dispersion may be depressurized while stirring to evaporate and remove the organic solvent. The latter two methods may be used in combination with the first method. The drying atmosphere in which the colored fine particle dispersion is sprayed is generally air, nitrogen, carbon dioxide, a gas obtained by heating combustion gas, etc., and in particular, various air streams heated to a temperature equal to or higher than the boiling point of the highest boiling point solvent used. The desired quality can be obtained sufficiently by short-term treatment with a spray dryer, belt dryer, rotary kiln, etc. By the above method, a colored fine particle dispersion liquid can be obtained.
[0077] (agglomeration process) Next, the resulting colored fine particle dispersion is agglomerated with stirring until the particles reach a desired particle size. To achieve flocculation, existing methods such as adding a flocculant or adjusting the pH can be used. When adding a flocculant, it may be added as is, but it is preferable to add the flocculant in an aqueous solution, as this can prevent localized high concentrations. It is also preferable to add the flocculant salt gradually while monitoring the particle size of the colored particles.
[0078] The temperature of the dispersion during aggregation is preferably near the Tg of the resin used. If the liquid temperature is too low, aggregation does not proceed very well, resulting in poor efficiency, whereas if the liquid temperature is too high, the aggregation rate increases, resulting in the generation of coarse particles and a deterioration in particle size distribution.
[0079] When the target particle size is reached, aggregation is stopped. Methods for stopping aggregation include adding a salt with a low ionic valence or a chelating agent, adjusting the pH, lowering the temperature of the dispersion, or adding a large amount of aqueous medium to dilute the concentration. By the above method, a dispersion of colored aggregated particles can be obtained.
[0080] In the aggregation step, a wax may be added as a release agent. In this case, the wax may be mixed with a dispersion liquid in which the wax is dispersed in an aqueous medium or with the colored fine particle dispersion liquid, and then the mixture may be aggregated to obtain aggregated particles in which the wax and crystalline resin are uniformly dispersed.
[0081] (Flocculant) As the flocculant, a known flocculant can be used, for example, a metal salt of a monovalent metal such as sodium or potassium, a metal salt of a divalent metal such as calcium or magnesium, or a metal salt of a trivalent metal such as iron or aluminum.
[0082] (fusion process) Next, the obtained aggregated particles are fused by heat treatment to reduce unevenness and to make them spherical. Fusion can be performed by heating the dispersion of the colored aggregated particles while stirring. The temperature of the liquid is preferably near a temperature above the Tg of the resin used.
[0083] (Shelling process) In the shelling step, a shell layer is formed on the spheronized particles obtained in the fusion step. The method for forming the shell layer is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the shell layer includes a method in which spherical particles having a desired particle size are produced in a fusion step, and then an amorphous resin is added, and the aggregating step and the fusion step are repeated to form the shell layer.
[0084] (Washing and drying process) The toner particle dispersion obtained by the above method contains sub-materials such as coagulated salts in addition to the toner particles, so washing is performed to extract only the toner particles from the dispersion. Methods for washing the toner particles include centrifugation, reduced pressure filtration, and filter press, but are not particularly limited in the present invention. Any of these methods can obtain a cake of toner particles, but if the toner particles cannot be sufficiently washed in one operation, the obtained cake may be dispersed again in an aqueous solvent to form a slurry, and the process of extracting the toner particles by any of the above methods may be repeated, or if washing is performed by reduced pressure filtration or filter press, a method may be adopted in which the aqueous solvent is penetrated into the cake to wash out the sub-materials embraced by the colored resin particles. The aqueous solvent used for this washing is water or a mixed solvent obtained by mixing water with an alcohol such as methanol or ethanol, but it is preferable to use water in consideration of costs and environmental loads due to wastewater treatment.
[0085] Since the washed toner particles contain a large amount of the aqueous medium, the aqueous medium can be removed by drying to obtain only the toner particles. As a drying method, a dryer, a vacuum freeze dryer, a reduced pressure dryer, a stationary shelf dryer, a movable shelf dryer, a fluidized bed dryer, a rotary dryer, an agitator dryer, or other dryer can be used. It is preferable to dry the dried toner particles until the moisture content is finally less than 1%. In addition, if the colored resin particles after drying are softly aggregated and cause inconvenience in use, the softly aggregated particles may be broken down using a device such as a jet mill, a Henschel mixer, a super mixer, a coffee mill, an Auster blender, or a food processor.
[0086] (Annealing process) When a crystalline resin is added, annealing after drying causes phase separation between the amorphous resin and the crystalline resin, improving fixability. Specifically, this can be done by storing the toner at a temperature near the Tg for 10 hours or more.
[0087] (External addition process) In order to impart fluidity, chargeability, cleaning properties, etc. to the toner particles obtained in the present invention, inorganic fine particles, polymeric fine particles, cleaning assistants, etc. may be added or mixed thereto. Specific mixing means include a method in which an impact force is applied to the mixture by blades rotating at high speed, a method in which the mixture is introduced into a high-speed air current, accelerated, and the particles collide with each other or the composite particles with an appropriate collision plate, etc. Examples of equipment include an Angmill (manufactured by Hosokawa Micron Corporation), a modified I-type mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, a hybridization system (manufactured by Nara Machinery Works, Ltd.), a Kryptron system (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar.
[0088] (External additives) The primary particle diameter of the inorganic fine particles is preferably 5 nm to 2 μm, and more preferably 5 nm to 500 nm. 2 / g~500m 2 / g. The proportion of the inorganic fine particles used is preferably 0.01 to 5 mass % of the toner. Specific examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride.
[0089] Examples of polymeric fine particles include polymer particles made of polystyrene, methacrylate or acrylate copolymers obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization, polycondensation systems such as silicone, benzoguanamine, and nylon, and thermosetting resins.
[0090] Such fluidizing agents are surface-treated to increase hydrophobicity and prevent deterioration of flow properties and charging properties even under high humidity. Examples of preferred surface treatment agents include silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, and modified silicone oils.
[0091] Examples of cleaning improvers for removing the developer remaining on the photoconductor or primary transfer medium after transfer include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, and polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles. The polymer fine particles preferably have a relatively narrow particle size distribution and a volume average particle size of 0.01 μm to 1 μm.
[0092] Since the resin particles according to one embodiment have the above-mentioned properties, they can be effectively used as materials for image formation, such as toner, developer, toner set, toner storage unit, and image forming apparatus.
[0093] <Toner> The toner according to an embodiment includes the resin particles according to an embodiment, and may be made of the resin particles according to an embodiment. By using the resin particles according to one embodiment in a toner, the environmental impact is reduced, and even if a plant-derived resin is used, it is possible to provide an image having excellent low-temperature fixing property and charging property, and excellent image quality.
[0094] <Developer> The developer according to an embodiment includes the toner according to an embodiment, and may include other components, such as a carrier, which are appropriately selected as necessary. This allows the developer to have excellent transferability, chargeability, and the like, and to stably form high-quality images. The developer may be a one-component developer or a two-component developer. However, when used in high-speed printers that correspond to the recent improvements in information processing speed, a two-component developer is preferable from the viewpoint of improving the developer life.
[0095] When the toner according to one embodiment is used in a single-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, and toner filming on the developing roller and toner adhesion to components such as blades that thin the toner layer are reduced, resulting in high-quality images being obtained in the developing device.
[0096] When the developer according to the embodiment is used as a two-component developer, it can be mixed with a carrier and used as a developer. When the toner according to the embodiment is used as a two-component developer, the particle size of the toner is small even if the toner is balanced over a long period of time, and good and stable developability and images can be obtained even when the toner is stirred for a long period of time in a developing device.
[0097] The content of the carrier in the two-component developer can be appropriately selected depending on the purpose, but is preferably 90 parts by mass to 98 parts by mass, and more preferably 93 parts by mass to 97 parts by mass, relative to 100 parts by mass of the two-component developer.
[0098] The developer according to an embodiment can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.
[0099] [Career] The carrier is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the carrier has a core material and a resin layer (coating layer) that coats the core material.
[0100] (Core material) The material of the core material is not particularly limited and can be appropriately selected according to the purpose. For example, manganese-strontium-based material of 50 emu / g to 90 emu / g, manganese-magnesium-based material of 50 emu / g to 90 emu / g, etc. can be mentioned. In order to ensure image density, it is preferable to use high magnetization materials such as iron powder of 100 emu / g or more, magnetite of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetization materials such as copper-zinc-based materials of 30 emu / g to 80 emu / g, because it can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for high image quality. These materials may be used alone or in combination of two or more.
[0101] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 μm to 150 μm, more preferably 40 μm to 100 μm. If the volume average particle diameter is 10 μm or more, the amount of fine powder in the carrier increases, and the magnetization per particle decreases, which can effectively prevent the problem of carrier scattering. On the other hand, if it is 150 μm or less, the specific surface area decreases, which can cause toner scattering, and in full color with many solid parts, the problem of poor reproduction of the solid parts can be effectively prevented.
[0102] (Resin layer) The resin layer can contain a resin and other components as necessary. The resin used in the resin layer can be a known material that can impart the necessary electrostatic property. Specifically, it is preferable to use a silicone resin, an acrylic resin, or a combination of these. In addition, the composition for forming the resin layer preferably contains a silane coupling agent. The average thickness of the resin layer is preferably 0.05 μm to 0.50 μm.
[0103] (Measurement method)
[0104] <Calculation and analysis methods for PET of toner components> The blending amount of the PET may be calculated by any method. For example, the toner is separated by gel permeation chromatography (GPC) or the like, and each of the separated components is subjected to the analysis method described below to calculate the mass ratio of the components. In addition, gas chromatography mass spectrometry at 300°C using a reaction reagent (10% tetramethyl ammonium hydroxide (TMAH) / methanol solution) can be used to estimate the main components from the soft decomposition of the ester bonds in the resin structure through methylation, and quantitative analysis can be performed by drawing a calibration curve of TICC intensity.
[0105] Separation of each component by GPC can be carried out, for example, by the following method. In GPC measurements using THF (tetrahydrofuran) as the mobile phase, The desired molecular weight is determined by the full integral of the elution curve. The fractions corresponding to the portions are pooled together. The combined eluate is concentrated and dried using an evaporator, and the solid content is dehydrated. Dissolve in a heavy solvent such as tetrahydrofuran or deuterated THF. 1 H-NMR measurement and integral of each element From the ratio, the ratio of the constituent monomers of the resin in the eluted components is calculated. Another method is to concentrate the eluate and then hydrolyze it with sodium hydroxide, etc. The decomposition products are then subjected to qualitative and quantitative analysis using high performance liquid chromatography (HPLC) etc. The constituent monomer ratio is calculated by the above.
[0106] <<Means for separating toner components>> An example of a means for separating each component when analyzing the toner will be described in detail below. First, 1 g of toner is put into 100 mL of THF, and the mixture is stirred for 30 minutes at 25° C. to obtain a solution in which the soluble matter is dissolved. This is filtered through a membrane filter with an opening of 0.2 μm to obtain the THF-soluble portion of the toner. Next, this is dissolved in THF to prepare a sample for GPC measurement, and is injected into the GPC used for measuring the molecular weight of each of the above-mentioned resins. Meanwhile, a fraction collector is placed at the eluate outlet of the GPC to collect the eluate at predetermined counts, and the eluate is obtained at 5% area ratios from the start of elution (the rise of the curve) of the elution curve.
[0107] Next, for each elution, 30 mg of the sample is dissolved in 1 mL of deuterated chloroform, and 0.05 vol. % of tetramethylsilane (TMS) is added as a standard substance. The solution is filled into a 5 mm diameter glass tube for NMR measurement, and a spectrum is obtained by 128 accumulations at 23° C. to 25° C. using a nuclear magnetic resonance apparatus (JNM-AL400 manufactured by JEOL Ltd.). The monomer composition and composition ratio of the PET resin and the like contained in the toner can be determined from the peak integral ratio of the obtained spectrum.
[0108] <Radioisotope 14 How to measure C concentration> Radiocarbon isotopes in toner 14 The C concentration was measured by radiocarbon dating. The toner was burned and the CO2 (carbon dioxide) was reduced to obtain C (graphite). 14 The C concentration was measured using AMS (Accelerator Mass Spectroscopy, Beta Analytic).
[0109] <Confirmation of core-shell structure> [TEM observation and measurement] The toner thus prepared is embedded in an epoxy resin and hardened. Ultrathin sections (approximately 100 nm thick) of the toner are prepared using an ultramicrotome (Leica ULTRACUT UCT, diamond knife used). The sample is exposed to ruthenium tetroxide, osmium tetroxide, or another staining agent, and the crystalline polyester resin phase is stained to distinguish it from the other parts. The exposure time is adjusted appropriately depending on the contrast during observation. The crystalline polyester resin phase is often observed as a lamellar structure. It is then observed with a transmission electron microscope (JEM-2100, JEOL) at an accelerating voltage of 100 kV. Depending on the composition of the crystalline polyester resin and non-crystalline polyester resin, it may be possible to distinguish them without staining, in which case they are evaluated without staining. It is also possible to impart compositional contrast by other means such as selective etching, and after such pretreatment, the crystalline polyester resin part may be evaluated by observing with a transmission microscope.
[0110] (Toner storage unit) The toner storage unit in the present invention refers to a unit having a function of storing toner and storing the toner. Examples of the toner storage unit include a toner storage container, a developing unit, and a process cartridge. The toner storage container refers to a container that stores toner. The developing device has a means for containing toner and developing the toner. The process cartridge is a cartridge that integrates at least an image carrier and a developing means, contains toner, and is detachably mountable to an image forming apparatus. The process cartridge may further include at least one selected from a charging means, an exposure means, and a cleaning means.
[0111] (Image forming device) Next, one embodiment of the method for forming an image by the image forming apparatus of the present invention will be described. The following description will be given with reference to Fig. 1. Although a printer is shown as an example of the image forming apparatus of the present embodiment, the image forming apparatus is not particularly limited as long as it is capable of forming an image using toner, such as a copier, a facsimile, or a multifunction machine. The image forming apparatus includes a paper feed section 210, a conveying section 220, an image creating section 230, a transfer section 240, and a fixing unit 250. The paper feed section 210 includes a paper feed cassette 211 in which the paper P to be fed is stacked, and a paper feed roller 212 that feeds the paper P stacked in the paper feed cassette 211 one sheet at a time.
[0112] The conveying section 220 includes a roller 221 that conveys the paper P fed by the paper feed roller 212 toward the transfer section 240, a pair of timing rollers 222 that hold the leading end of the paper P conveyed by the roller 221 and wait to send the paper to the transfer section 240 at a predetermined timing, and a paper discharge roller 223 that discharges the paper P with the color toner image fixed thereto onto a paper discharge tray 224.
[0113] The image creating section 230 includes, spaced at a predetermined interval from left to right in the figure, an image forming unit Y that forms an image using a developer containing yellow toner, an image forming unit C that uses a developer containing cyan toner, an image forming unit M that uses a developer containing magenta toner, an image forming unit K that uses a developer containing black toner, and exposure devices (233Y, 233C, 233M, 233K). Incidentally, when referring to any one of the image forming units (Y, C, M, K), it is referred to as an image forming unit.
[0114] The developer contains toner and carrier. Four image forming units (Y, C, M, K) are essentially identical in mechanical construction, except for the developer used.
[0115] The transfer unit 240 includes a drive roller 241 and a driven roller 242, an intermediate transfer belt 243 that can rotate counterclockwise in the figure as the drive roller 241 is driven, primary transfer rollers (244Y, 244C, 244M, 244K) arranged opposite the photosensitive drums (231Y, 231C, 231M, 231K) across the intermediate transfer belt 243, and secondary opposing roller 245 and secondary transfer roller 246 arranged opposite each other across the intermediate transfer belt 243 at the transfer position of the toner image to paper.
[0116] The fixing unit 250 includes a fixing belt 251 with an internal heater for heating the paper P, and a pressure roller 252 that forms a nip by applying pressure to the fixing belt 251 so as to be rotatable. This applies heat and pressure to the color toner image on the paper P, fixing the color toner image. The paper P with the fixed color toner image is discharged to a paper discharge tray 224 by a paper discharge roller 223, completing a series of image formation processes.
[0117] (Process cartridge) The process cartridge according to the present invention is molded so as to be detachably mountable to various image forming apparatuses, and has at least an electrostatic latent image carrier for carrying an electrostatic latent image, and a developing means for developing the electrostatic latent image carried on the electrostatic latent image carrier with the developer of the present invention to form a toner image. The process cartridge of the present invention may further have other means as necessary.
[0118] The developing means includes at least a developer container that contains the developer of the present invention, and a developer carrier that carries and transports the developer contained in the developer container. The developing means may further include a regulating member or the like for regulating the thickness of the developer carried.
[0119] An example of a process cartridge according to the present invention is shown in Fig. 2. The process cartridge 110 has the photosensitive drum 10, a corona charger 58, a developing device 40, a transfer roller 80 and a cleaning device 90. EXAMPLES
[0120] The present invention will be described in more detail below based on examples, but the technical scope of the present invention is not limited to the following examples in any way. In the following description, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0121] <Synthesis of amorphous polyester resin A-1> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived propylene glycol, recycled resin-derived terephthalic acid, and plant-derived succinic acid were charged so that the molar ratio of terephthalic acid to succinic acid (terephthalic acid / succinic acid) was 86 / 14, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.1. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C, normal pressure, and 4 hours to obtain [amorphous polyester resin A-1].
[0122] <Synthesis of amorphous polyester resin B-1> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived propylene glycol, bisphenol A propylene oxide 2 mole adduct, recycled resin-derived terephthalic acid, and plant-derived succinic acid and adipic acid were added in a molar ratio of propylene glycol to bisphenol A ethylene oxide 2 mole adduct (propylene glycol / bisphenol A ethylene oxide 2 mole adduct) of 20 / 80, and terephthalic acid to succinic acid in a molar ratio of ( The mixture was charged with a 70 / 30 mixture of terephthalic acid / succinic acid, and a molar ratio of OH / COOH between hydroxyl groups and carboxyl groups of 1.1. This was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and this was reacted at 180°C, normal pressure, and for 4 hours to obtain [Amorphous Polyester Resin B-1].
[0123] <Synthesis of amorphous polyester resin B-2> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived propylene glycol, bisphenol A propylene oxide 2 mole adduct, recycled resin-derived terephthalic acid and isophthalic acid, and plant-derived succinic acid and adipic acid were added in a molar ratio of 20 / 80 (propylene glycol / bisphenol A ethylene oxide 2 mole adduct) and 20 / 80 (terephthalic acid / succinic acid). The mixture was charged with a 60 / 6 / 14 / 20 ratio of hydroxyl groups to carboxyl groups (acid / isophthalic acid / succinic acid / adipic acid) and a molar ratio of OH / COOH of 1.1, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at normal pressure and 230°C for 8 hours, and then reacted for another 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin component, and reacted at 180°C, normal pressure, for 4 hours to obtain [Amorphous Polyester Resin B-2].
[0124] <Synthesis of amorphous polyester resin B-3> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived propylene glycol, bisphenol A propylene oxide 2 mole adduct, recycled resin-derived terephthalic acid, and plant-derived succinic acid were mixed in a molar ratio of propylene glycol to bisphenol A ethylene oxide 2 mole adduct (propylene glycol / bisphenol A ethylene oxide 2 mole adduct) of 30 / 70 and a molar ratio of terephthalic acid to succinic acid of 100 / 100. The mixture was charged with a mixture of 86 / 14 hydroxyl and carboxyl acids (succinic acid / succinic acid) and 1.1 molar ratio of OH / COOH between hydroxyl and carboxyl groups, and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and reacted at 180°C, normal pressure, for 4 hours to obtain [Amorphous Polyester Resin B-3].
[0125] <Synthesis of amorphous polyester resin B-4> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived propylene glycol, bisphenol A propylene oxide 2 mole adduct, recycled resin-derived ethylene glycol, recycled resin-derived terephthalic acid, isophthalic acid, and plant-derived succinic acid were added, and the molar ratio of propylene glycol, bisphenol A ethylene oxide 2 mole adduct, and ethylene glycol (propylene glycol / bisphenol A ethylene oxide 2 mole adduct / ethylene glycol) was 30 / 60 / 10, and the molar ratio of terephthalic acid, succinic acid, and isophthalic acid was 30 / 60 / 10. The acid was charged in a molar ratio (terephthalic acid / succinic acid / isophthalic acid) of 80 / 14 / 6, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.1. Furthermore, 10% of flake-shaped recycled PET was charged and reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours. After further reacting for 4 hours at a reduced pressure of 10 mmHg to 15 mmHg, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the reaction was continued at 180°C, normal pressure, and for 4 hours to obtain [Amorphous Polyester Resin B-4].
[0126] <Synthesis of amorphous polyester resin B-5> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, propylene glycol, bisphenol A propylene oxide 2 mole adduct, terephthalic acid, and succinic acid were added to a 4-neck flask so that the molar ratio of propylene glycol to bisphenol A ethylene oxide 2 mole adduct (propylene glycol / bisphenol A ethylene oxide 2 mole adduct) was 60 / 40, and the molar ratio of terephthalic acid to succinic acid (terephthalic acid / succinic acid) was 80 / 100. The mixture was charged so that the ratio of hydroxyl groups to carboxyl groups was 6 / 14, and the molar ratio of OH / COOH between the hydroxyl groups and the carboxyl groups was 1.1. This was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and this was reacted at 180°C, normal pressure, for 4 hours to obtain [Amorphous Polyester Resin B-5].
[0127] <Synthesis of amorphous polyester resin (MB) for masterbatches> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, terephthalic acid derived from plant-derived propylene glycol recycled resin and succinic acid derived from plant were charged so that the molar ratio of terephthalic acid to succinic acid (terephthalic acid / succinic acid) was 86 / 14 and the molar ratio of hydroxyl groups to carboxyl groups (OH / COOH) was 1.1. The mixture was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and further reacted at a reduced pressure of 10 mmHg to 15 mmHg for 4 hours. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C, normal pressure, and 4 hours to obtain [Masterbatch Amorphous Polyester Resin MB].
[0128] <Synthesis of crystalline polyester resin C-1> In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, plant-derived 1,8-octanedicarboxylic acid and plant-derived ethylene glycol were charged so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.1, and trimellitic anhydride was added in a molar ratio of 0.047. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at 180°C for 10 hours, then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours to obtain [Crystalline Polyester Resin C-1].
[0129] <Synthesis of crystalline polyester resin C-2> [Crystalline polyester resin C-2] was obtained in the same manner as in the synthesis of [Crystalline polyester resin C-1], except that plant-derived 1,4-butanediol was used instead.
[0130] <Synthesis of crystalline polyester resin C-3> Crystalline polyester resin C-3 was obtained in the same manner as in the synthesis of Crystalline polyester resin C-1, except that plant-derived 1,10-decanedicarboxylic acid and plant-derived 1,4-butanediol were used instead.
[0131] <Synthesis of Crystalline Polyester Resin C-4> Crystalline polyester resin C-4 was obtained in the same manner as the synthesis of [Crystalline polyester resin C-1], except that succinic acid derived from plants and 1,4-butanediol derived from plants were used instead.
[0132] <Synthesis of Crystalline Polyester Resin C-5> Crystalline polyester resin C-5 was obtained in the same manner as the synthesis of [Crystalline polyester resin C-1], except that decanediol derived from plants was used instead.
[0133] <Preparation of Crystalline Polyester Resin Dispersion 1> 350 parts of [Crystalline polyester resin C-1], 210 parts of methyl ethyl ketone, and 61.8 parts of isopropyl alcohol were placed in a separable flask. After thoroughly mixing and dissolving them at 50 °C, 16.24 parts of a 10% aqueous ammonia solution was added dropwise. The heating temperature was lowered to 65 °C, and while stirring, ion-exchanged water was added dropwise using a liquid delivery pump at a liquid delivery rate of 8 g / min. After the liquid became uniformly turbid, the liquid delivery rate was increased to 12 g / min. When the total liquid volume reached 1400 parts, the addition of ion-exchanged water was stopped. Thereafter, the solvent was removed under reduced pressure to obtain [Crystalline polyester resin dispersion 1].
[0134] <Preparation of Crystalline Polyester Resin Dispersions 2 to 5> Crystalline polyester resin dispersions 2 to 5 were obtained in the same manner as the preparation of [Crystalline polyester resin dispersion 1], except that [Crystalline polyester resin C-1] was changed to [Crystalline polyester resins C-2 to C-5].
[0135] <Preparation of WAX Dispersion> 180 parts of ester wax (NOF Corp., WE-11, synthetic wax made from plant-derived monomers, melting point 67°C) and 17 parts of an anionic surfactant (Dai-ichi Kogyo Seiyaku Corp., Neogen SC, sodium dodecylbenzenesulfonate) were added to 720 parts of ion-exchanged water. The mixture was dispersed in a homogenizer while heated to 90°C to obtain [WAX Dispersion W-1]. The solids concentration of the resulting wax dispersion was 25%.
[0136] <Preparation of Masterbatch MB-1> 1,200 parts of water, 500 parts of carbon black (Printex35, manufactured by Dexa) [DBP oil absorption = 42 mL / 100 mg, pH = 9.5], and 500 parts of [Masterbatch amorphous polyester resin MB] were added and mixed in a Henschel mixer (manufactured by Nippon Coke and Engineering Co., Ltd.). The mixture was kneaded using two rolls at 150°C for 30 minutes, then cooled by rolling and pulverized in a pulverizer to obtain [Masterbatch MB-1].
[0137] Example 1 <Preparation of oil phase> 100 parts of [Crystalline Polyester Resin Dispersion 1], 50 parts of [WAX Dispersion W-1], 650 parts of [Amorphous Polyester Resin B-1], and 100 parts of [Masterbatch MB-1] were placed in a container and mixed at 5,000 rpm for 60 minutes using a TK Homomixer (manufactured by Primix Corporation) to obtain [Oil Phase 1]. The blending amount indicates the blending amount of solid content in each raw material.
[0138] <Preparation of aqueous phase> 990 parts of water, 20 parts of sodium dodecyl sulfate, and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid, which was designated as [aqueous phase 1].
[0139] <Emulsification> 900 parts of [Oil Phase 1] was stirred at 8,000 rpm with a TK Homomixer, 20 parts of 28% aqueous ammonia was added, and mixed for 10 minutes. Then, 1,200 parts of [Aqueous Phase 1] was gradually added dropwise to obtain [Emulsified Slurry 1].
[0140] <Solvent removal> [Emulsified slurry 1] was placed in a container equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 180 minutes to obtain [solvulant-removed slurry 1].
[0141] <Shell preparation> In the preparation of the oil phase, 100 parts of [Crystalline polyester resin dispersion 1], 50 parts of [WAX dispersion W-1], 650 parts of [Amorphous polyester resin B-1], and [Master batch MB-1] were replaced with [Amorphous polyester resin A-1], and in the preparation of the water phase, 20 parts of sodium dodecyl sulfate were replaced with 0 parts, and ethyl acetate was replaced with MEK. [Shell desolvated slurry 1] was obtained in the same manner as in Example 1.
[0142] <Agglutination> 100 parts of 3% magnesium chloride solution was added dropwise to 900 parts of [Shell Desolvation Slurry 1] and stirred for another 5 minutes, then the temperature was raised to 60°C, and when the particle size reached 5.0 μm, 200 parts of [Shell Desolvation Slurry 1] was added dropwise, 100 parts of 3% magnesium chloride solution was further added dropwise and stirred for 5 minutes, after which 50 parts of sodium sulfate aqueous solution was added to terminate the aggregation process, and [Aggregated Slurry 1] was obtained.
[0143] <Fusion> [Agglomerated slurry 1] was heated to 70° C. with stirring, and cooled when the desired average circularity of 0.957 was reached, to obtain [Dispersed slurry 1].
[0144] <Washing and drying> [Dispersion Slurry 1] 100 parts was filtered under reduced pressure, (1) 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% aqueous sodium hydroxide solution was added to the filter cake of (1), mixed with a TK homomixer (at 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid was added to the filter cake of (2), and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4): 300 parts of ion-exchanged water is added to the filter cake of (3), mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. The above steps (1) to (4) were repeated twice to obtain [Filter Cake 1]. The [filter cake 1] was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a mesh with 75 μm openings to obtain [resin particle base body 1].
[0145] <External additive processing process> 100 parts of [Resin particle base 1] was mixed with 2.0 parts of hydrophobic silica (HDK-2000, manufactured by Clariant) as an external additive in a Henschel mixer, and passed through a 500 mesh sieve to obtain [Resin particle 1].
[0146] (Examples 2 to 7, Comparative Examples 1 to 3) Resin particles 2 to 10 were prepared in the same manner as resin particle 1, except that the types of crystalline polyester resin C and amorphous polyester resin B added in each step were changed as shown in Table 1, to prepare resin particles 2 to 10.
[0147] [Table 1]
[0148] The environmental ratio, low-temperature fixability, heat-resistant storage stability, and environmental compatibility of these resin particles were evaluated. The evaluation methods are described below, and the evaluation results are shown in Table 2.
[0149] (Evaluation method) <Low temperature fixability> A carrier used in imagio MP C5503 (manufactured by Ricoh Company, Ltd.) and the resin particles obtained above were mixed so that the concentration of the resin particles was 5% by mass, to obtain a developer. After putting the developer into the unit of the imagio MP C5503 (manufactured by Ricoh Co., Ltd.), a rectangular solid image of 2 cm x 15 cm was printed on PPC paper type 6000<70W>A4 T (manufactured by Ricoh Co., Ltd.) with a toner adhesion of 0.40 mg / cm 2At this time, the surface temperature of the fixing roller was changed, and it was observed whether or not cold offset occurred, in which a residual image of a solid image was fixed in a place other than the desired place, and the low-temperature fixing property was evaluated. [Evaluation Criteria] A: Less than 110℃ B: 110℃ or higher and less than 120℃ C: 120℃ or higher but lower than 130℃ D: 130℃ or more
[0150] <Heat-resistant storage stability> Evaluation of thermal storage stability The toner was filled into a glass container and left in a thermostatic chamber at 50° C. for 24 hours. The toner is cooled to 24° C., and the penetration is measured by a penetration test (JIS K2235-1991). The criteria for judging the heat preservation property based on the penetration are as follows: [Evaluation Criteria] A:25mm or more B: 10mm or more and less than 25mm C: Less than 10 mm
[0151] <Environmental friendliness> The ratio of the total mass of biomass-derived resin and recycled resin to the mass of resin particles (see the calculation formula below) was defined as the "resin ratio," and the environmental compatibility of this resin ratio was evaluated according to the following evaluation criteria. Resin Ratio = [(biomass-derived resin + recycled resin) / resin particles] x 100 (Evaluation Criteria) A:Resin ratio 50% or more B: Resin ratio: 40% or more but less than 50% C: Resin ratio: 30% to less than 40% D: Resin ratio less than 30% The results are shown in Table 2.
[0152] [Table 2]
[0153] For example, aspects of the present invention are as follows. (1) At least C2-C4 linear aliphatic alcohol / C 10 -C 12 Resin particles containing a resin C derived from biomass consisting of a linear aliphatic acid and a resin B containing a component derived from polyethylene terephthalate (PET) and / or polybutylene terephthalate (PBT), The resin particles have a core-shell structure consisting of a core resin and a shell resin, The core resin comprises a crystalline resin, The resin particles are characterized in that the total ratio of the resin C and the resin B in 100% by mass of the resin particles is 30% by mass or more. (2) Resin particles according to (1) above, in which Resin B contains structural units derived from terephthalic acid and structural units derived from isophthalic acid, and the ratio of the structural units derived from isophthalic acid to the structural units derived from terephthalic acid is 1% or more. (3) The resin particles according to (1) or (2) above, wherein the total proportion of the resin C and the resin B in 100% by mass of the resin particles is 50% by mass or more. (4) A toner comprising the resin particles according to any one of (1) to (3) above. (5) A toner storage unit, characterized in that it stores the toner described in (4) above. (6) an electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image bearing member; a developing unit including a toner, the developing unit developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image; a transfer means for transferring the toner image formed on the electrostatic latent image carrier onto a surface of a recording medium; A fixing unit that fixes the toner image transferred onto the surface of the recording medium, An image forming apparatus, wherein the toner is the toner described in (4) above. (7) forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image; a transfer step of transferring the toner image formed on the electrostatic latent image carrier onto a surface of a recording medium; A fixing step of fixing the toner image transferred onto the surface of the recording medium, The image forming method, wherein the toner is the toner described in (4) above. [Explanation of symbols]
[0154] 10 Photoconductor drum 40 Developer 58 Corona charger 80 Transfer roller 90 Cleaning Equipment 110 Process cartridge 210 Paper feed section 211 Paper feed cassette 212 Paper feed roller 220 Conveyor 221 Lola 222 Timing roller 223 Paper ejection roller 224 Paper output tray 230 Image creation section 231Y, 231C, 231M, 231K Photoconductor Drum 233Y, 233C, 233M, 233K Exposure Unit 240 Transcription Unit 241 Drive roller 242 Driven roller 243 Intermediate transfer belt 244Y, 244C, 244M, 244K Primary transfer roller 245 Secondary opposing roller 246 Secondary transfer roller 250 Fixing unit 251 Fixing belt 252 Pressure roller P paper L exposure [Prior art documents] [Patent documents]
[0155] [Patent Document 1] Patent No. 4512631 [Patent Document 2] Patent No. 5717615 [Patent Document 3] JP 2009-37206 A
Claims
1. At least, C. 2 -C 4 Linear aliphatic alcohol / C 10 -C 12 and a resin B containing a component derived from polyethylene terephthalate (PET) and / or polybutylene terephthalate (PBT), The resin particles have a core-shell structure consisting of a core resin and a shell resin, The core resin comprises a crystalline resin, The resin particles are characterized in that a total ratio of the resin C and the resin B is 30% by mass or more in 100% by mass of the resin particles.
2. 2. The resin particles according to claim 1, wherein the resin B contains structural units derived from terephthalic acid and structural units derived from isophthalic acid, and the ratio of the structural units derived from isophthalic acid to the structural units derived from terephthalic acid is 1% or more.
3. The resin particles according to claim 1 or 2, wherein a total ratio of the resin C and the resin B in 100% by mass of the resin particles is 50% by mass or more.
4. A toner comprising the resin particles according to claim 1 or 2.
5. A toner storage unit containing the toner according to claim 4.
6. An electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image bearing member; a developing unit including a toner, the developing unit developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image; a transfer means for transferring the toner image formed on the electrostatic latent image carrier onto a surface of a recording medium; A fixing unit that fixes the toner image transferred onto the surface of the recording medium, 5. An image forming apparatus, comprising the toner according to claim 4.
7. an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image; a transfer step of transferring the toner image formed on the electrostatic latent image carrier onto a surface of a recording medium; A fixing step of fixing the toner image transferred onto the surface of the recording medium, 5. An image forming method, comprising the toner according to claim 4.
Citation Information
Patent Citations
Service tray
JP1982017615A
Toner, its manufacturing method, two-component developer, developing apparatus, and image forming apparatus
JP2009037206A
Toner, method for manufacturing the toner, two-component developer, developing apparatus, and image forming apparatus
JP4512631B2